2009
DOI: 10.1002/ibd.20880
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune signaling by Toll-like receptor-4 (TLR4) shapes the inflammatory microenvironment in colitis-associated tumors

Abstract: Patients with ulcerative colitis are at increased risk for developing colorectal cancer. We have shown that TLR4 is over-expressed in human colitis-associated cancer (CAC) and that mice deficient in TLR4 are markedly protected against colitis-associated neoplasia. We wished to elucidate the specific contributions of TLR4 signaling by myeloid cells and colonic epithelial cells (CEC) in colitis-associated tumorigenesis. TLR4-deficient mice or wild-type littermates (WT) were transplanted with bone marrow (BM) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 50 publications
6
102
0
Order By: Relevance
“…The increased cell proliferation observed in both the small intestine ( Figure 6A) and colon (data not shown) may also be linked to inflammation (e.g., cytokine stimulation), as has been reported by others (60,61), or alternatively, to compensatory mechanisms that respond to excessive cell damage and exfoliation (30,47). Increased cell migration may be inflammation induced as well (62).…”
Section: Figuresupporting
confidence: 61%
“…The increased cell proliferation observed in both the small intestine ( Figure 6A) and colon (data not shown) may also be linked to inflammation (e.g., cytokine stimulation), as has been reported by others (60,61), or alternatively, to compensatory mechanisms that respond to excessive cell damage and exfoliation (30,47). Increased cell migration may be inflammation induced as well (62).…”
Section: Figuresupporting
confidence: 61%
“…4D). Cyclooxygenase 2 (COX-2) and inducible nitric oxide synthase (iNOS) are previously reported to be upregulated in CAC and accelerate the tumor formation, 16,34-36 but we did not observe the statistically significant difference of them in WSX-1 KO and WT IECs with CAC model (Fig. 4D).…”
Section: Wsx-1 Deficiency Leads To Higher Level Of Inflammatory Cytokmentioning
confidence: 58%
“…But excessive TLR activation is often consequent in pathogenesis, previous study indicated that rather than immune cells, the function of TLR signaling pathway in IECs is much more significant in CAC. 16 Here, we report its anti-inflammatory function which exerts on TLR ligand-induced inflammation in intestinal epithelia cells. In our study, increased tumor incidence and tumor load were observed in WSX-1 deficient mice, along with enhanced tumor cell proliferation and MDSC accumulation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations